2016
DOI: 10.1016/j.bbr.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

N270 sensitivity to conflict strength and working memory: A combined ERP and sLORETA study

Abstract: The event-related potential N270 component is known to be an electrophysiological marker of the supramodal conflict processing. However little is know about the factors that may modulate its amplitude. In particular, among all studies that have investigated the N270, little or no control of the conflict strength and of the load in working memory have been done leaving a lack in the understanding of this component. We designed a spatial audiovisual conflict task with simultaneous target and cross-modal distract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
4
13
0
Order By: Relevance
“…Besides, only the REST-obtained N270 showed a significant increment in the task-irrelevant feature change. This finding was compatible with the delayed behavioral performance, and therefore is consistent with the view that frontal conflict control mechanism characterized by N270 is responsible for regulating external behavioral conflicts (Zhang et al, 2008 ; Yin et al, 2012 ; Scannella et al, 2016 ). Obviously, the interpretation of the ERP results varied with the references used, and only the REST provided the closest approximation to the relevant literatures and the delayed behavior performance.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Besides, only the REST-obtained N270 showed a significant increment in the task-irrelevant feature change. This finding was compatible with the delayed behavioral performance, and therefore is consistent with the view that frontal conflict control mechanism characterized by N270 is responsible for regulating external behavioral conflicts (Zhang et al, 2008 ; Yin et al, 2012 ; Scannella et al, 2016 ). Obviously, the interpretation of the ERP results varied with the references used, and only the REST provided the closest approximation to the relevant literatures and the delayed behavior performance.…”
Section: Discussionsupporting
confidence: 89%
“…Cortical source localization evidences showed that N270 may generate from the anterior cingulate cortex (ACC) (Yin et al, 2012 ). In consideration of a strong connectivity existing between ACC and the dorsolateral prefrontal cortex (DLPFC) (Wang et al, 2010 ), it was proposed that N270 reflects the downstream process (Zhang et al, 2008 ; Scannella et al, 2016 ). This mechanism is based upon the afferent ACC signals and takes place within the DLPFC to generate an appropriate behavior response (Scannella et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important processing that moderates the cognitive outcome in these studies is matching comparison, operationalized by the degree to which the compared dimensions are incongruous to each other. The electrophysiological findings typically relating to the incongruity of the processing of visual metaphor are those by Scannella et al (2016), who claimed that N270 is sensitive to the conflict strength. In the context of advertising, Szubielska et al (2012) found that the amplitudes of information conflicting components (N270, P300, and N400) were sensitive to incongruity between the product category and the previously presented brand.…”
Section: Pictorial Metaphor and Incongruitymentioning
confidence: 99%
“…In previous studies, when presenting a mismatch stimulus to the preceded stimulus to participants, a negative ERP component potential with peak latency of approximately 270ms (N270) was recorded [23], [24]. N270 was explored by S1-S2 paradigm and evoked by the mismatch between the presentation in working memory and the following perceptual input [25]. Cognitive basis of N270 is processing of working memory representation conflict [25].…”
Section: In Facial and Expression Recognition In Other Psychiatric DImentioning
confidence: 99%